Harga, Lokasi dan Kualitas Pelayanan Penentu Minat Beli Konsumen - Sadiyah, Halimatus (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2021)
The purpose of this study was to describe and determine the effect of price, location and service quality on consumer buying interest in the BUMDesa Pengalangan Menganti Gresik business market. The sample used was 60 respondents with a questionnaire data instrument. The analysis used is multiple linear regression analysis. The results showed that the price partially had no effect on consumer buying interest in the BUMDesa Penganti Gresik Business Market, the location partially had a significant positive effect on consumer buying interest in the BUMDesa Pengalangan Business Market and the service quality partially had a significant positive effect on consumer buying interest. at the BUMDesa Penganti Gresik Business Market. Simultaneously, price, location and service quality have a significant positive effect on consumer buying interest in the Penganti Gresik BUMDesa Business Market.